2015
DOI: 10.5199/ijsmart-1791-874x-20b
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Lifestyle and Dropout: Exploring the Experience of Amateur Athletes in Competitive Sport

Abstract: This study explores the relationship between amateur athletes' leisure lifestyle and dropout. Athletes often neglect aspects of their life outside of sport, as training, practicing, and competing takes up most of their time. Having an unbalanced leisure lifestyle can have negative effects on well-being. To examine this issue, a multiple qualitative case study approach was utilized. Participants chosen for this study were ten ex-competitive amateur athletes from Canada, who competed at a high-performance level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Research in which ex-sportspeople, both professional and amateur took part, carried out in Canada in 2015, presented a picture of their behaviours in the psychological context. The results indicated that the lifestyles of sportspeople in the course of their careers were at less than optimal level (MacCosham, Patry, Beswick, Gravelle, 2015). However, after finishing their career, the sportspeople changed their behaviours and perception of the world.…”
Section: Discussionmentioning
confidence: 96%
“…Research in which ex-sportspeople, both professional and amateur took part, carried out in Canada in 2015, presented a picture of their behaviours in the psychological context. The results indicated that the lifestyles of sportspeople in the course of their careers were at less than optimal level (MacCosham, Patry, Beswick, Gravelle, 2015). However, after finishing their career, the sportspeople changed their behaviours and perception of the world.…”
Section: Discussionmentioning
confidence: 96%
“…Los argumentos presentados fueron organizados a partir de lo económico ya que, desde este plano, incluyendo aspectos sociales y de salud, se señala que la forma actual de apoyo a los atletas podría configurarse como una barrera para el desarrollo deportivo (Guirola Gómez et al, 2018). Este emplazamiento podría complementarse con las ideas de Burlot et al (2018), en la medida que al no mediar un contrato de trabajo por el dinero que reciben los atletas mes a mes, podría presentarse un estado de tensión permanente que generaría efectos negativos en el bienestar (MacCosham et al, 2015).…”
Section: Discussionunclassified
“…En general, los resultados también son coherentes con lo señalado por Pérez-Rivases et al (2017) respecto a que la carrera dual es un proceso complejo. No obstante, los datos proponen una dimensión que va más allá de las cualidades psicológicas individuales propuestas por algunos estudios (Surujlal et al, 2013;Burlot et al, 2018;MacCosham et al, 2015;Knight et al, 2018;Hollings et al, 2014) y se podría manifestar que en Chile no se estaría desarrollando una buena práctica de carrera dual que facilite el complemento entre el estudio o el trabajo con la dedicación al deporte. Específicamente, cuando un deportista declaró que por decidir terminar su carrera profesional fue expulsado del programa, ofrece información para expresar que en el país esta modalidad reproduce la desigualdad y la inequidad en el acceso al estudio, al trabajo y/o al deporte ya que, según su relato, no se podría compatibilizar el deporte con una carrera profesional.…”
Section: Discussionunclassified
“…However, the target group in most of these studies includes non-athletes [ 11 , 14 , 16 19 ]. In another set of studies, factors related to athletes’ lifestyles, such as addiction [ 20 ], exercise addiction [ 21 ], leisure and dropout [ 22 ], health management in life [ 23 ], health challenges, and gender differences [ 24 ] have been emphasized. As Kahma (2012) believes, in lifestyle studies and theories, sports subjects are often marginalized and ignored [ 15 ].…”
Section: Introductionmentioning
confidence: 99%